A descriptive study on the possible presence of bacterial contaminants in seven repacked dental alginate impression materials - Gonzales, Reginald Christopher C.
Seven (7) different brands of repacked dental alginate impression materials were tested for the possible presence of bacterial contaminants. Based on the results from the microbiological tests done, bacteria was found to be present, particularly Staphylococcus aureus and Pseudomonas aeruginosa. A supplementary test was also done, only to show the presence, too, of yeasts and fungus.